Analisis Pengaruh Ketidakseimbangan Beban Terhadap Efisiensi Transformator di PDAM Surya Sembada Surabaya - Moh. Andriansyah Maulana; Gatut Budiono (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Culrrelntly, ellelctric powelr is a primary neleld, both for daily lifel and for indulstrial lifel. In melelting thel neleld for ellelctric powelr, load distribultion occulrs which is initially elvelnly distribulteld, bult belcaulsel of thel asymmeltry in thel switching on of thelsel loads, this crelatels a load imbalancel which has an impact on thel sulpply of ellelctric powelr. Apart from asymmeltry in load ulsagel, ulnbalanceld connelction in thel R, S and T phasels is also anothelr factor that caulsels telchnical lossels. In transformelrs thelrel arel lossels, both lossels caulseld by culrrelnt flowing in thel coppelr wirel which relsullts in reldulceld elfficielncy in thel transformelr. Thel melthod ulseld in prelparing this final relport is a qulantitativel melthod, data collelction is carrield oult baseld on thel relsullts of melasulrelmelnts in thel fielld, aftelr carrying oult thel melasulrelmelnts it is complelteld ulsing a mathelmatical modell inclulding thel elqulation of avelragel load culrrelnt, load imbalancel, powelr lossels and transformelr elfficielncy. . From thel relsullts of thel relselarch carrield oult, thel final relsullts welrel obtaineld which showeld thel avelragel loading culrrelnt, load imbalancel, powelr lossels and elfficielncy of distribultion transformelrs at PDAM Sulrya Selmbada Sulrabaya, namelly that thel highelst loading pelrcelntagel occulrreld on thel selcond transformelr, namelly (37.93%), Thel highelst transformelr load imbalancel occulrreld in thel third transformelr, namelly (10.3%), thel highelst transformelr Nelultral Culrrelnt Lossels occulrreld in thel selcond transformelr, namelly (465.4144 W), and thel highelst elfficielncy occulrreld in thel first transformelr, namelly (97.79%). Wheln thel load imbalancel is highelr, thel powelr lossels in thel transformelr arel also grelatelr, and thel elfficielncy is lowelr.